Proposta de implantação da norma ABNT NBR ISO 9001:2008 no centro de serviços de uma empresa especializada em equipamentos topográficos - Vasconcelos, Aislan Policarpo Barretos (2013)
This work refers to the proposed implementation of ABNT NBR ISO 9001:2008 in central services of a company that sells and provides technical support for surveying and geodetic equipment. The Service Center studied company does not have a Quality Management System, documented procedures or even mapping of processes that directly influence the quality of services provided. The market trend shows the need to tailor the procedures and structure of the company to issue the Certificate M, which presents values of the angles, distances, their errors and standard deviations measured by the equipment when maintenance is performed. For the issuance of the Certificate M, the release of the company represented by the Service Center, which requires as a prerequisite the ISO 9001:2008 certification is required. For such a study of the standard in order to tailor the Service Center with respect to meeting the requirements will be done as well as providing the necessary documentation. With the implementation of the standard is intended to establish a Quality Management System that can ensure the ability of the company to make quality services and thereby achieve authorization from the company represented to the issuance of the Certificate M demanded by their customers.